2016
DOI: 10.1016/j.pharep.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective mechanism of Coenzyme Q10 (CoQ10) against PTZ induced kindling and associated cognitive dysfunction: Possible role of microglia inhibition

Abstract: The present study suggests the involvement of microglia inhibition in the protective effect of CoQ10 in PTZ induced kindling in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…. This increase has also been reported in previous studies [39,40]. In the present study,the administration of CBZ by either route significantly decreased TNF-α content in the brain tissue as compared to the PTZ control group.…”
Section: Behavioral Assessment By Elevated Plus Maze Testsupporting
confidence: 92%
“…. This increase has also been reported in previous studies [39,40]. In the present study,the administration of CBZ by either route significantly decreased TNF-α content in the brain tissue as compared to the PTZ control group.…”
Section: Behavioral Assessment By Elevated Plus Maze Testsupporting
confidence: 92%
“…Previous reports have demonstrated that CoQ10 prevents memory and cognitive deficits under different conditions [61-65]. The present findings indicate that CoQ10 can prevent the memory and cognitive impairment induced by DM.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, subcutaneous administration of DMSO in P7 C57/BL/6By mice is reported to induce microglial activation in the brain ( Saito et al, 2015 ) and administration of sub-toxic doses of paraquat in mice are reported to result in microglial activation prior to neurodegeneration ( Purisai et al, 2007 ). In addition, a microglial inhibitory mechanism has recently been proposed in CoQ10 mediated protection against Aβ(1–42) induced cognitive dysfunction ( Meneses et al, 2015 ) and pentylenetetrazol induced kindling epilepsy in mice ( Bhardwaj and Kumar, 2016 ). In addition, with accumulating evidence for the involvement of amyloid beta in glaucoma pathology ( Guo et al, 2007 , Ito et al, 2012 , Nizari et al, 2016 ) and growing recognition of mechanistic similarities between glaucoma and Alzheimer's disease ( Gupta et al, 2016 , Sivak, 2013 ), modulation of microglial activation by CoQ10 could contribute to the reported neuroprotective effects of this agent.…”
Section: Discussionmentioning
confidence: 99%